NARCOTICS PREVENTION AMONG PRISONERS BY NATIONAL NARCOTICS AGENCY (BNN) - Hibnu Nugroho (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Nowadays, Indonesia has high number of narcotics users. It includes narcotics abuse inside Correctional Institution. The research investigates whether law enforcement policy in narcotics eradication among prisoners has been effectively implemented or not and what impediments encountered by the National Narcotics Agency (BNN) in upholding law enforcement to fight against narcotics among prisoners. The research applied empirical juridical approach particularly analytical descriptive. The key informants in this research are Central Java BNN and Central Java Drugs Penitentiary. This research employed qualitative descriptive analysis while the content analysis applied legal interpretation, principles of law and legal theories. This belongs to Research and Development (R&D) and the Theory of Law Enforcement Factors by Soerjono Soekanto. Narcotics prevention by National Narcotics Agency in prison is not effectively implemented due to lack of a number of officials or guards to supervise the prisoners.Keywords: prevention, narcotics, Correctional Institution